Apoptosis: Dual role in aetiology and cure - Aye Aye Wynn; Ohnmar Myint; Nang Khin Mya (Penerbit UMS, 2019)
Apoptosis is a programmed cell death which occurs following a variety of stimuli. Physiologically the process is important for morphogenesis of organs and homeostasis of different types of cells. Apoptotic cell death is responsible for a variety of pathologic states such as elimination of cell death in mutated cells, infected cells, tumour cells and transplant rejection well as the pathological atrophy. In this review, there is discussion about the control of apoptosis, detection methods of apoptosis, its association with infectious and non-communicable diseases. Intracellular microorganisms survive through inhibition of host cell apoptosis as well as they destroy the parenchymal cells causing impaired functions. It plays important role in tumourigenesis. There are possible therapeutic roles of drugs that modify apoptosis in human diseases.